The Influencing Factors toward Universitas Warmadewa Student Interests in Using Mobile Commerce - Desak Rurik Pradnya Paramitha Nida; I Made Dwi Sumba Wirawan; I Made Dwi Harmana (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
Mobile commerce provides an overview of the development of electronic commerce. The rapid growth of the mobile phone population has accompanied the emergence and development of wireless technology which has made mobile commerce an important part of existing business strategies. The purposes of this study are to treasure the empirical evidence on the factors that influence the interest of mobile commerce users as input for e-commerce providers and users as well as to describe the reflection of the development and needs conditions of the business world, especially in the mobile commerce sector. This study uses primary data collected using a questionnaire, as a data collection method. Data collection method was a survey method through a questionnaire. study belongs to a qualitative research with Multiple Linear Regression Analysis technique. The results showed that the users of mobile commerce have been increasing in number. Besides that, the perceived usefulness, perceived ease of use, perceived cost, perceived social influence, perceived trust, perceived privacy, and perceived security had an impact on the user’s interests in using the mobile commerce.